INDEPENDENT PELLET FEED PRODUCTION SKILLS IN IMPROVING THE INCOME OF FRESHWATER FISH FARMERS IN KLABAT VILLAGE, DIMEMBE DISTRICT, NORTH MINAHASA REGENCY - Wullur, Mozes M.; Pinontoan, Marien; Wullur, Norry (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
Livelihood education for the community is considered strategic in facing the demands of increasingly competitive changes in society’s civilization, including the ability of farmers in the business of making freshwater fish feed in the form of pellets independently. This study aims to analyze and describe the motivation, process and results of independent learning of farmers in producing freshwater fish feed pellets at the research location. This study uses a naturalistic qualitative approach with observation techniques, in-depth interviews and documentation of informants 4 farmers, 2 fisheries extension officers, 4 collectors/retailers of freshwater fish production, village heads and 1 community leader which was carried out for 4 months, the results obtained; 1. The motivation for independent learning of farmers in learning to make freshwater fish feed pellets includes; a. curiosity to learn how to make carp, tilapia and mujair feed pellets, b. accelerating the fish growth process, c. increasing fish harvest production and d. increasing farmer business income. 2. The independent learning process for making freshwater fish feed pellets includes; learning through YouTube videos, b. Observing the pellet making process at the Freshwater Fish Cultivation Center in Tatelu Village, Dimembe District, North Minahasa Regency, c. Seeing friends making freshwater fish feed pellets, d. Reading books on freshwater fish feed pellet making techniques and e. Group learning. 3. The results of independent learning to make freshwater fish feed pellets are; a. the acquisition of knowledge, experience and insight as well as farmer skills to make freshwater fish feed pellets independently in togetherness. b. The existence of farmers who are ready to be a source of learning for other farmers, c. There is an acceleration of maintenance time and increased harvest production of carp and tilapia cultivation from the aspect of fish weight and farmer income as informants. d. An independent freshwater fish feed pellet production farmer group has been formed at the research location. It is recommended for farmers to continue to develop towards independent production marketing in the form of farmer groups. For the relevant government to support the production of freshwater fish feed pellets. 3. The university, especially UNIMA, should continue to provide assistance in the form of fostered villages through fostered groups of freshwater fish farming farmers at the research location.